2024
DOI: 10.1002/ehf2.14696
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models for patients suffering a heart failure with a preserved ejection fraction: a systematic review

Ying‐Ying Jia,
Nian‐Qi Cui,
Ting‐Ting Jia
et al.

Abstract: The purpose of this study was to systematically review the development, performance, and applicability of prognostic models developed for predicting poor events in patients with heart failure with preserved ejection fraction (HFpEF). Databases including Embase, PubMed, Web of Science Core Collection, the Cochrane Library, China National Knowledge Infrastructure, Wan Fang, Wei Pu, and China Biological Medicine were queried from their respective dates of inception to 1 June 2023, to examine multivariate models f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…published in the current issue of ESC Heart Failure evaluates selected multifactorial algorithms predicting outcome in HFpEF. 2 After a literature search, the authors identified 16 studies testing 39 prognostic models for inclusion in the analysis. External validation was used to confirm the predictive performance of assessed strategies in only 10 of the 16.…”
mentioning
confidence: 99%
“…published in the current issue of ESC Heart Failure evaluates selected multifactorial algorithms predicting outcome in HFpEF. 2 After a literature search, the authors identified 16 studies testing 39 prognostic models for inclusion in the analysis. External validation was used to confirm the predictive performance of assessed strategies in only 10 of the 16.…”
mentioning
confidence: 99%